1991
DOI: 10.1128/jb.173.2.587-600.1991
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Escherichia coli phn (psiD) gene cluster in assimilation of phosphorus in the form of phosphonates, phosphite, Pi esters, and Pi

Abstract: The phn (psiD) gene cluster is induced during Pi limitation and is required for the use of phosphonates (Pn) as a phosphorus (P) source. Twelve independent Pn-negative (Pn-) mutants have lesions in the phn gene cluster which, as determined on the basis of recombination frequencies, is larger than 10 kbp. This distance formed the basis for determining the complete DNA sequence of a 15.6-kbp BamHI Interestingly, all Pn-mutations abolish the use not only of Pn but also of Pt, in which P is in the +3 oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
136
0
4

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(148 citation statements)
references
References 53 publications
6
136
0
4
Order By: Relevance
“…It is important to note that using ITC measurements, we failed to detect any binding of the E. coli PhnD protein either to phosphite or to phosphate. These were previously suggested to be P substrates in E. coli (Metcalf and Wanner, 1991;Rizk et al, 2006)). Interestingly, both Prochlorococcus PhnD proteins showed a completely different specificity range: one (PhnD2) binds strongly only to MPn, EPn and inorganic phosphite, whereas the other (PhnD1) binds strongly to inorganic phosphite and with very weak affinities to MPn and phosphate (see Table S1 for dissociation constants).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that using ITC measurements, we failed to detect any binding of the E. coli PhnD protein either to phosphite or to phosphate. These were previously suggested to be P substrates in E. coli (Metcalf and Wanner, 1991;Rizk et al, 2006)). Interestingly, both Prochlorococcus PhnD proteins showed a completely different specificity range: one (PhnD2) binds strongly only to MPn, EPn and inorganic phosphite, whereas the other (PhnD1) binds strongly to inorganic phosphite and with very weak affinities to MPn and phosphate (see Table S1 for dissociation constants).…”
Section: Resultsmentioning
confidence: 99%
“…A promoter similar to the pho box encountered in E. coli 41 TCAAGC, which is very similar to the pho box reported in E. coli 41 . This system is known to strongly regulate the expression of Pst, derepressing it only in cases of low Pi concentrations 40,42 . Therefore, it is likely that the Pst system is repressed for most of the EBPR cycle, with the possible exception of the end of the aerobic period when Pi concentrations drop to uM levels.…”
Section: Phosphate Transportersmentioning
confidence: 99%
“…and other heterotrophic bacteria 10,12 , as well as marine autotrophs such as Trichodesmium 19 , have been shown to use MPn as a sole P source. In these organisms, MPn degradation proceeds via the C-P lyase pathway and is induced by P i starvation 12,[20][21][22][23] . Building on these findings, studies by Karl et al 9 and Martínez et al 17 showed that when surface seawater is amended with glucose and a nitrogen source (to stimulate P i -limiting conditions), MPn hydrolysis and CH 4 production proceeds at rates that scale inversely with the addition of exogenous P i .…”
mentioning
confidence: 99%
“…strain HTCC7211 (str. HTCC7211), isolated from the North Atlantic Ocean in the Sargasso Sea 32 , encodes for additional proteins involved in organophosphorus transport (PhnCDEE 2 ) 20 and phosphonate utilization (PhnGHIJKLNM), suggesting that the two organisms have evolved different adaptive strategies for P acquisition related to niche partitioning 14 .…”
mentioning
confidence: 99%